Is assessment fair? - Nisbet, Isabel; Shaw, Stuart D., 1962- (London : SAGE Publications Ltd, 2020)
Fairness in educational assessment has become a major talking point and allegations that assessments are unfair are commonplace on social media and in the press. But what does fairness mean in practice and how can we evaluate it? This book offers a timely and necessary investigation, exploring the concept through the lenses of: measurement theory, social justice, the law and philosophy in order to put forward a template for fairness in educational assessment. Drawing on international examples from the UK, US, Australia and South East Asia, this book offers a commentary on fairness that is highly relevant to the changing context of assessment today. This book will be of interest to anyone with a professional or academic interest in educational assessment, to education policymakers and to all who are working to make assessment fair.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Examinations; Education -- Moral and ethical aspects